5p deletions: Current knowledge and future directions. (3rd August 2015) - Nguyen, Joanne M.; Qualmann, Krista J.; Okashah, Rebecca; Reilly, AmySue; Alexeyev, Mikhail F.; Campbell, Dennis J.; Cody, Jannine DeMars; Battaglia, Agatino; Hale, Daniel Esten
<x xml:space="preserve">Abstract</x> Disorders resulting from 5p deletions (5p−) were first recognized by Lejeune et al. in 1963 [Lejeune et al. (1963); C R Hebd Seances Acad Sci 257:3098–3102]. 5p− is caused by partial or total deletion of the short arm of chromosome 5. The most recognizable phenotype is characterized by a high‐pitched cry, dysmorphic features, poor growth, and developmental delay. This report reviews 5p− disorders and their molecular basis. Hemizygosity for genes located within this region have been implicated in contributing to the phenotype. A review of the genes on 5p which may be dosage sensitive is summarized. Because of the growing knowledge of these specific genes, future directions to explore potential targeted therapies for individuals with 5p− are discussed. © 2015 Wiley Periodicals, Inc.